Dzyaduk H.O. Conceptual foundations for strategy of small and medium-sized agrobusiness development in Ukraine - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The article offers conceptual foundations of the strategy of development of small and medium-sized agrarian business in Ukraine, which include the formulation of the vision of the future, the mission, the strategic goal, the system of strategic directions, stages and mechanisms of implementation, and the scenarios of further transformations, the system of monitoring and evaluation of the ef ciency of the implementation to ensure the reproductive potential of the industry as the result of effective actions of public authorities